PENGAWASAN DAN PERTANGGUNGJAWABAN BADAN PENGELOLA INVESTASI DANANTARA DALAM PENGELOLAAN RISIKO KERUGIAN INVESTASI KEUANGAN NEGARA - Ni'matul Maula, Putri; Danie, Elsha Victoria; Irawan, Muhammad Hafizh Athallah; Lumban Gaol, Samuel Rainhard (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2025)
The Daya Anagata Nusantara Investment Management Agency (BPI Danantara) was established to manage state investments and assets based on Government Regulation No. 10 of 2025 on the Organization and Governance of the Daya Anagata Nusantara Investment Management Agency, aiming to maximize government investment and encourage national economic growth. This research highlights the importance of transparency, oversight and accountability in managing the risk of state financial investment losses. BPI Danantara is required to prepare an annual performance report audited by an independent auditor and report periodically to the Supervisory Board, including agencies, such as KPK, BPK, and OJK. Despite the regulations, there are still concerns about the effectiveness of supervision and potential conflicts of interest within the Supervisory Board. Responsibility for investment losses falls entirely on BPI Danantara, not the state, leaving a gap in the moral accountability of investment managers. The purpose of this writing is to analyze the Supervisory Transparency Mechanism in the Daya Anagata Nusantara Investment Management Agency on the Implementation of State Financial Investments and the Legal Liability of the Daya Anagata Nusantara Investment Management Agency for the Risk of State Financial Investment Losses. This research uses a juridical-normative approach to analyze relevant regulations and emphasizes the importance of transparency and accountability mechanisms in state financial management. It is expected that BPI Danantara can become a better model of financial management and contribute to national economic growth in accordance with further provisions in Government Regulation Number 10 of 2025 concerning Organization and Governance of the Daya Anagata Nusantara Investment Management Agency.